Verbal-Visual Mediation: cultural artifacts of power and control for studies of school context in Applied Linguistics research - Neto, Adolfo Tanzi (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
In this article we explore the data and theoretical discussions of a larger research (Tanzi Neto, 2016, 2017) and present one of the analysis tools of the research group NUVYLA-CNPq (Nucleus of Studies and Research of Vygotsky School in Applied Linguistics), created in 2018. In the framework of a dialogue between Vygotsky, Bakhtin and Bernstein, the research group seeks to demonstrate how the dimensions of verbal-visual utterances (artifacts) practiced in school spaces - embedded of multiple languages - mediate the formation of human consciousness. For this discussion, we analyze the verbal-visuality of different exhibitors from two public school contexts in Brazil. In the ﬁrst one, of social base of more hierarchical discursive relations, that is to say, of verbal-visual utterances more controlled, the school space is not seen, by its participants, as a place to reach new projects of life, neither as a space of belonging or as recognized social positionings. In the second context, of social base of less controlled relations of power and control, that is, that provides the voice, identity and social position of its participants, we observe a reconﬁguration of the dialogical and axiological positions of its participants, creating a school social context of belonging and recognition of its members to achieve future projects.